Discharge Planning Terhadap Kesiapan Klien Menghadapi Pemulangan Dengan Ulkus Diabetikum - Suwarly Mobiliu; Paulus Pangalo; Nurafni Suid (Poltekkes Kemenkes Gorontalo, 2020)
Background: Discharge planning or discharge planning is a process of starting the client from getting health services followed by continuity of care both in the healing process and in improving health status until the patient feels ready to return to his environment.Objective: This study aims to determine the effect of discharge planning on the client's readiness to face discharge with diabetic ulcers in the operating room of Toto Kabila Hospital, Bone Bolango Regency.Method: The design in this research is pre-experiment with 20 people taking purposive samplingResults: The results showed that after discharge planning the client's readiness level increased as many as 15 people (75%) with a readiness level of 4, and as many as 5 people (25%) with a readiness level 3. Based on the SPSS analysis test using the Wilcoxon Signed Rank Test, it was obtained P value = 0.000 so p value < 0.05. Then the results obtained Ha or H1 is accepted.Conclusion: These results indicate that there is a significant effect of discharge planning on the client's readiness to face discharge with diabetic ulcers in the operating room of the Toto Kabila Hospital, Bone Bolango Regency.